Implementation of a Pelvic Floor Physical Therapy Program for Transgender Women Undergoing Gender-Affirming Vaginoplasty. Issue 5 (May 2019) - Jiang, Da David; Gallagher, Sandra; Burchill, Laura; Berli, Jens; Dugi, Daniel
Abstract : OBJECTIVE: To describe the incidence of pelvic floor dysfunction in transgender women undergoing gender-affirming vaginoplasty and outcomes in a program providing pelvic floor physical therapy (PT). METHODS: We conducted a retrospective, single-institution study on vaginoplasty patients between May 1, 2016, and February 28, 2018; all were referred for pelvic floor PT. We reviewed medical records for baseline demographics, medical comorbidities, prior surgeries, insurance data, attendance at pelvic floor PT, and dilation success at 3 and 12 months. RESULTS: Seventy-two of 77 patients (94%) attended pelvic floor PT at least once. Preoperative pelvic floor PT identified a high incidence of potential problems: 42% had pelvic floor dysfunction, 37% had bowel dysfunction. Of those patients found to have dysfunction preoperatively, the rate of resolution by the first postoperative visit of pelvic floor and bowel dysfunction were 69% and 73%, respectively. There were significantly lower rates of pelvic floor dysfunction postoperatively for those patients who attended pelvic floor PT both preoperatively and postoperatively compared with only postoperatively (28% vs 86%, P =.006). Patients reporting a history of abuse had a significantly higher rate of preoperative pelvic floor muscle dysfunction (91% vs 31%, P <.001). Successful dilation at 3 months in all patients was 89%. CONCLUSION: Pelvic floor physical therapists identify and help patients resolve pelvic floor-related problems before and after surgery. We find strong support for pelvic floor PT for patients undergoing gender-affirming vaginoplasty. Abstract : The high incidence of pelvic floor dysfunction in patients undergoing gender-affirming vaginoplasty is improved with pelvic floor physical therapy.